Review of Error Correction in 2D Shingled Magnetic Detection - M.B Abdulrazaq; Abdullahi, Hassan; B.O Sadiq; H. Zaharuddeen; U. Abubakar; M.D Almustapha (ELEKTRIKA- Journal of Electrical Engineering, 2023)
This paper presents the review of error correction in 2D shingled magnetic detection. Shingled magnetic recording is one of the techniques proposed in literature for increasing the storage density of magnetic hard disk drive (HDD) due to the number of overwhelming advantages of shingled writing. The success of this technique lies with a proper signal processing and data update approach. In this paper, shingled magnetic recording and two-dimensional magnetic recording has been studied and the current researches done in the two areas has been reviewed with emphasis on elimination of inter-track-interference and inter-symbol-interference. In the reviewed articles studied, a summary was provided on each article depicting the technique adopted and the performance metrics of each of the articles. Summary was provided at the end of the article on the techniques reviewed based on the existing body of knowledge.